Draft Seventh Five Year Plan (1985-90) and Annual Plan (1985-86) Volume-X Hill Areas Government of Assam - Planning Commission (Planning Commission, 1985)
The Local allocation for the Sixth Five Year Plan (1980-85) for General Education (Hill Areas) is Rs. 616.10 lakhs under state plan against the tentative outlay of Rs. 500.00 lakhs and Rs. 340.72 lakhs under Additive plan against the tentative outlay of Rs. 100.00 lakhs.
Office of the Development Commissioner for the Hill Areas of Assam